Socioeconomic Status and Cognitive Function in Children With HIV: Evidence From the HIV-Associated Neurocognitive Disorders in Zambia (HANDZ) Study. (1st January 2022) - Mbewe, Esau G.; Kabundula, Pelekelo P.; Mwanza-Kabaghe, Sylvia; Buda, Alexandra; Adams, Heather R.; Schneider, Colleen; Potchen, Michael J.; Mweemba, Milimo; Mathews, Manoj; Menon, J. Anitha; Wang, Bo; Baseler, Travis; et al.
Abstract : Background: Multiple previous studies have identified a detrimental effect of pediatric HIV on cognitive function. Socioeconomic status (SES) is one of the strongest predictors of cognitive performance and may affect the relationship between HIV and cognition. Methods: As part of the ongoing HIV-Associated Neurocognitive Disorders in Zambia (HANDZ) study, a prospective cohort study, we recruited 208 participants with HIV and 208 HIV-exposed uninfected controls, all aged 8–17 years. A standardized questionnaire was administered to assess SES, and all participants had comprehensive neuropsychological testing. An NPZ8 score was derived as a summary measure of cognitive function. Logistic regression and linear regression were used to model the relationship between SES and cognitive function, and mediation analysis was used to identify specific pathways by which SES may affect cognition. Results: Children with HIV performed significantly worse on a composite measure of cognitive function (NPZ8 score −0.19 vs. 0.22, P < 0.001) and were more likely to have cognitive impairment (33% vs. 19%, P = 0.001). Higher SES was associated with reduced risk of cognitive impairment (odds ratio 0.8, 95% confidence interval: 0.75–0.92, P < 0.001) in both groups, with similar effects in children with HIV and HIV-exposed uninfected groups. SES was more strongly correlated with NPZ8 score in children with HIV than in uninfected controls (Pearson's R 0.39 vs. 0.28), but predicted NPZ8 in both groups. Mediation analysis suggested that the effect of SES on cognition was most strongly mediated through malnutrition. Conclusions: Cognitive function is strongly correlated with SES in children with HIV, suggesting a synergistic effect of HIV and poverty on cognitive function. Abstract : Supplemental Digital Content is Available in the Text.